Functional Analysis of the Acinetobacter baumannii XerC and XerD Site-Specific Recombinases: Potential Role in Dissemination of Resistance Genes - David L. Lin; German M. Traglia; Rachel Baker; David J. Sherratt; Maria Soledad Ramirez; Marcelo E. Tolmasky (MDPI AG, 2020)
Modules composed of a resistance gene flanked by Xer site-specific recombination sites, the vast majority of which were found in Acinetobacter baumannii, are thought to behave as elements that facilitate horizontal dissemination. The A. baumannii xerC and xerD genes were cloned, and the recombinant clones used to complement the cognate Escherichia coli mutants. The complemented strains supported the resolution of plasmid dimers, and, as is the case with E. coli and Klebsiella pneumoniae plasmids, the activity was enhanced when the cells were grown in a low osmolarity growth medium. Binding experiments showed that the partially purified A. baumannii XerC and XerD proteins (XerCAb and XerDAb) bound synthetic Xer site-specific recombination sites, some of them with a nucleotide sequence deduced from existing A. baumannii plasmids. Incubation with suicide substrates resulted in the covalent attachment of DNA to a recombinase, probably XerCAb, indicating that the first step in the recombination reaction took place. The results described show that XerCAb and XerDAb are functional proteins and support the hypothesis that they participate in horizontal dissemination of resistant genes among bacteria.